Analisis Tingkat Literasi Finansial Mahasiswa Manajemen Bisnis Syariah di STAI Al-Kifayah Riau: Konsep, Sikap, dan Perilaku - Arfah, Lita (Penerbit Goodwood, 2024)
Purpose: Students must have a good understanding of finance, especially when facing the challenges of financial management in today's era. The purpose of this study was to determine how proficient Sharia Business Management (MBS) students at STAI Al-Kifayah Riau are with basic financial concepts, attitudes, and behaviors related to finance. Methodology: This study was conducted using a quantitative approach through a survey. The stratified random sampling method consisted of 85 MBS students who were randomly selected. Data were collected through a financial literacy questionnaire distributed online via Google Form. Results: The results of the analysis showed that MBS students at STAI Al-Kifayah Riau had high financial literacy in basic financial concepts and products, with 17% in the high category, 28% in the medium category, and 55% in the low category. Financial attitudes, with 21% in the high category, 34% in the medium category, and 45% in the low category, and financial behavior, with 20% in the high category, 31% in the medium category, and 49% in the low category. Limitation: If the sample is only taken from one institution (STAI Al-Kifayah Riau), the results may not be generalizable to students in other institutions or different areas. Contribution: The results show that the majority of MBS students of STAI Al-Kifayah Riau do not understand financial concepts, attitudes, and behaviors. This suggests that education should be conducted to improve students' financial knowledge, especially by offering courses or training that focus more on financial management.